2019
DOI: 10.1016/j.mito.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Alternative NAD(P)H dehydrogenase and alternative oxidase: Proposed physiological roles in animals

Abstract: The electron transport systems in mitochondria of many organisms contain alternative respiratory enzymes distinct from those of the canonical respiratory system depicted in textbooks. Two of these enzymes, the alternative NADH dehydrogenase and the alternative oxidase, were of interest to a limited circle of researchers until they were envisioned as gene therapy tools for mitochondrial disease treatment. Recently, these enzymes were discovered in several animals. Here, we analyse the functioning of alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 130 publications
9
61
0
Order By: Relevance
“…AOX branches the mitochondrial respiratory chain, bypassing complexes III and IV in a non‐proton‐motive reaction that oxidizes ubiquinol directly by molecular oxygen (Rogov, Sukhanova, Uralskaya, Aliverdieva, & Zvyagilskaya, ). The gene for AOX is present in most groups of eukaryotes, including animals (McDonald & Gospodaryov, ), but has been lost from specific lineages during the course of evolution, notably from vertebrates and advanced insects. The reasons for its evolutionary loss or retention are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…AOX branches the mitochondrial respiratory chain, bypassing complexes III and IV in a non‐proton‐motive reaction that oxidizes ubiquinol directly by molecular oxygen (Rogov, Sukhanova, Uralskaya, Aliverdieva, & Zvyagilskaya, ). The gene for AOX is present in most groups of eukaryotes, including animals (McDonald & Gospodaryov, ), but has been lost from specific lineages during the course of evolution, notably from vertebrates and advanced insects. The reasons for its evolutionary loss or retention are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that AOX is in the genomes of multiple species of copepods from around the world that inhabit a wide variety of ecological niches (Table 2.) The first reports of AOX from arthropods were in the brine shrimp Artemia franciscana and putative sequences from other members of the Chelicerata, Hexapoda, and Crustacea (Rodriguez-Armenta et al, 2018;McDonald and Gospodaryov, 2018). It was previously hypothesized that AOX was not present in arthropods due to a gene loss event (McDonald et al, 2009), however, the above data refute this hypothesis.…”
Section: Discovery Of Aox In Copepods and The Phylum Arthropodamentioning
confidence: 93%
“…AOX has been identified in several animal species due to the presence of AOX DNA or mRNA sequences in public molecular databases (McDonald and Vanlerberghe, 2004;McDonald et al, 2009). Recent database searches have revealed the presence of AOX DNA or mRNA in the phyla Ctenophora, Platyhelminthes, Arthropoda, Tardigrada, Scalidophora, Brachiopoda, and Rotifera for the first time (McDonald and Gospodaryov, 2018). Experimental evidence for the expression of AOX mRNA exists for the sponge Ephydatia muelleri, and the molluscs Anadara ovalis, Crassostrea gigas, Crassostrea virginica, and Mercenaria mercenaria (McDonald et al, 2009;Liu and Guo, 2017).…”
Section: Aox In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These alternative enzymes possess some key properties that distinguish them from other mitochondrial complexes: they are single or oligo subunit, non-proton pumping enzymes, as the energy they convey during their activation does not support mitochondrial potential; they are not inhibited by cytochrome pathway inhibitors (e.g. rotenone and cyanide) and, in contrast to other mitochondrial complexes, they are not transmembrane proteins but are associated to either the inner or the outer surface of the inner mitochondrial membrane [6,7].…”
Section: Introductionmentioning
confidence: 99%